2011
DOI: 10.1007/s10545-011-9346-0
|View full text |Cite
|
Sign up to set email alerts
|

Parent‐reported benefits of flupirtine in juvenile neuronal ceroid lipofuscinosis (Batten disease; CLN3) are not supported by quantitative data

Abstract: Juvenile neuronal ceroid lipofuscinosis (JNCL; CLN3 disease; Batten disease) is an autosomal recessive neurodegenerative disease of childhood that typically presents at school age with vision loss followed by progressive cognitive decline, motor dysfunction, seizures, and behavior problems. No therapy has been shown to slow the progression of disease in JNCL patients, and all current treatments are symptomatic. Flupirtine has been shown in vitro to reduce apoptosis in CLN3 lymphocytes. Based on that preclinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…Also, retigabine is in trials for treatment of amyotrophic lateral sclerosis (Clinicaltrial.gov ID: NCT02450552). A case report on one case treated with flupirtine in NCL disease is published …”
Section: Discussionmentioning
confidence: 99%
“…Also, retigabine is in trials for treatment of amyotrophic lateral sclerosis (Clinicaltrial.gov ID: NCT02450552). A case report on one case treated with flupirtine in NCL disease is published …”
Section: Discussionmentioning
confidence: 99%
“…In addition, the UBDRS Behavioral Assessment subscale has been cross validated with the Achenbach Child Behavior Checklist, with r s ranging from 0.39 to 0.72 with related items [8]. The UBDRS has been used in studies to quantify decline in physical functioning [9], measure change in disease severity over time in longitudinal studies, to compare sex and genotype differences [8,10], and to determine treatment efficacy [11]. …”
Section: Methodsmentioning
confidence: 99%
“…70 Some parents giving the drug flupirtine to their children with juve nile CLN3 disease have anecdotally reported benefit; how ever, quantitative, See Online for appendix prospectively obtained data did not show any change in disease progression that could be attributed to this drug. 71 A clinical trial treat ing 19 children with juvenile CLN3 disease with a nonsteroidal immunosuppressive drug, mycophenolate mofetil, over two 8week treatment periods with a 4week intervening washout 68,69 showed that this drug was well tolerated, but there was no clinical benefit. 58 A trial in nine children with CLN1 disease that tested the com bination of phospho cysteamine and Nacetylcysteine, reported no clinical benefit (table 2).…”
Section: Pharmacological Approachesmentioning
confidence: 99%